Two-Dimensional Metal Organic Framework Nanosheets as Bifunctional Catalyst for Electrochemical and Photoelectrochemical Water Oxidation - Liu, Chang; Shen, Xiaochen; Johnson, Grayson; Zhang, Yulu; Zhang, Changlin; Chen, Jiafu; Li, Lingyan; Sheehan, Colton; Peng, Zhenmeng; Zhang, Sen (Frontiers in Chemistry, 2020)
Electrochemical (EC) and photoelectrochemical (PEC) water splitting represent promising strategies for renewable energy conversion and fuel production, and require design of efficient catalysts for the oxygen evolution reaction (OER). Herein, we report the synthesis of two-dimensional (2D) Co-based metal organic framework (Co-MOF) nanosheets and their bifunctional catalytic properties for both EC and PEC OER. Benefiting from the large surface area and abundant isolated metal active sites, the Co-MOF nanosheets exhibited excellent OER activity and stability. The efficient electron-hole generation and separation of the nanosheets, owing to dimensional confinement, contributed to an improved visible light response in PEC OER. This study presents a new strategy to design EC/PEC bifunctional catalyst utilizing unique structural and electronic features of 2D MOF.